CONSIDERABLE STRATEGIES OF TEACHING LARGE MULTI-LEVEL CLASSES: A NARRATIVE STUDY OF WHAT EFL TEACHERS SHOULD DO - Salwa Salwa (IJEE (Indonesian Journal of English Education), 2014)
Teaching classes in which there is a uniformity of learners‟ proficiency level is the most ideal environment in language classes since it enables teachers to apply appropriate teaching and learning strategies based on the individual student‟s level. However, in EFL settings, most teachers especially in school environments have to teach classes in which the learners have multiple levels of ability, since at schools, there is no placement test on students‟ ability of English as is usually done in private language institutions. This paper provides some useful strategies which can be applied by teachers in teaching classes where true and false beginners are within the same class. Applying these strategies is expected to assist weaker students to get benefit from interacting with stronger students without holding back the strong ones. Teaching English in the EFL context needs more efforts and persistence since the target language (TL) is not used in the daily conversation. In addition, it is common to find large and mixed- ability students in the EFL contexts, which management is surely not easy. Consequently, EFL teachers often find both true and false beginners in a classroom. According to Brown (2007) true beginners are students who do not have any knowledge of the target language, whereas false beginners are those who have previously studied the target language ( they have been familiar with alphabets, simple greetings, etc), but they remember only a little of what they have learned. Due to the characteristics of beginners who still have a high dependency on their teachers as a role model , the most suitable approach to be applied in this kind of class is the teacher-centered classroom (Brown, 2007). Therefore, in this novice stage, teachers play a significant role in helping the lower level students to improve their language skills. Since there are two levels of beginners in this kind of class, a good language teacher should apply some special techniques to successfully teach this mixed-ability class as teaching this kind of class needs more preparation berita terkini terbaru and special techniques than teaching in placed or streamed classes .I am going to provide some strategies which can be applied in teaching true and false beginners within a class.